Book Reviews. Issue 2 (1st October 2018) - Herrero, Carmen; Vecchi, Ilaria
Up Against the Wall: Re-imagining the U.S.–Mexico Border, Edward S. Casey and Mary Watkins (2014)Austin: University of Texas Press, 288 pp., ISBN 978-0-29275-841-4, p/bk, £20.99Cinema and Development in West Africa: Film as a Vehicle for Liberation, James E. Genova (2013)Bloomington: Indiana University Press, 222 pp., ISBN 978-0-25301-008-7, h/bk, £54